PELATIHAN KEWIRAUSAHAAN UNTUK MENINGKATKAN KEMAMPUAN PARA PELAKU USAHA KECIL DI BANDUNG - Maria Merry Marianti; Paulina Permatasari; Istiharini Istiharini; Probowo Erawan Sastroredjo; Natalia Christi (Universitas Sanata Dharma, 2021)
The purpose of this training is to increase the knowledge and abilities of novice entrepreneurs who are just starting out or small entrepreneurs who want to develop their business to be bigger and more planned. Improving the management capabilities of small entrepreneurs, can help them improve their business strategy, operations management, marketing, finance, human resources, and financial reports. The target is to increase the ability of novice entrepreneurs or small entrepreneurs, so that they are able to improve their business management, increase sales, and ultimately be able to increase the scale (size) of the company and the profit of the company in a sustainable manner. The training methods provided are in the form of presentations on how to make a business strategy, crisis management, marketing management during a crisis, how to calculate Cost of Goods Sold (COGS), how to make a Profit/Loss Report, and how to create Brand Rights. After attending the training for 2 months, all participants are required to create an initial Business Model Canvas. This business model is then gradually evaluated and redeveloped, resulting in continuous improvement.